Protein-protein Interaction Studies between TSHR Protein in Human and Photosystem II Protein D1 of Ulva fasciata using In silico Protocols - Archana G; Sundararaj R (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The most prevalent mutation in Hypothyroid Protein, TSHR impacts the course and prognosis of Hypothyroidism in human. We employ 3D in silico drug docking techniques to make the possible mutant TSHR interact with Photosystem II Protein D1 of Ulva fasciata. To carry out drug docking techniques, the translated amino acid sequence and three-dimensional chemical compound were obtained from the NCBI database. The use of sophisticated 3D molecular visualization tools was employed in post-docking experiments. The use of sophisticated 3D molecular visualization tools was employed in post-docking experiments. The docking study results unequivocally show that Photosystem II Protein D1 directly suppresses amino acid mutational sites. TSHR and Photosystem II Protein D1’s electrostatic force is depicted in a three-dimensional manner using notions from molecular dynamics techniques. In the end, we determined that Photosystem II Protein D1, a medicinal component of Ulva fasciata, helps in treating hypothyroidism. Hypothyroidism, being one of the major Endocrinological disorders, our research work helps to prove that the sea weed, Ulva fasciata can effectively act a novel therapeutic agent for treating this disorder.